The Barcelona-Asymptomatic Intracranial Atherosclerosis study: Subclinical intracranial atherosclerosis as predictor of long-term vascular events. (March 2019) - Planas-Ballvé, Anna; Crespo, Ane Miren; Aguilar, Lorena Martín; Hernández-Pérez, María; Canento, Tamara; Dorado, Laura; Alzamora, María T.; Torán, Pere; Pera, Guillem; Muñoz-Ortiz, Laura; Arenillas, Juan F.; Castañón, María; et al.
Abstract: Background and aims: Symptomatic intracranial atherosclerosis (ICAS) is associated with a high risk of stroke recurrence and occurrence of other vascular events. However, ICAS has been poorly studied from its asymptomatic stage. The objective of our study was to determine if subclinical intracranial atherosclerosis is associated with long-term incident vascular events in Caucasians. Methods: The Barcelona-Asymptomatic Intracranial Atherosclerosis (AsIA) Study is a population-based study that enrolled 933 subjects with a moderate-high vascular risk and without history of stroke or coronary disease, and determined the prevalence of asymptomatic ICAS and associated risk factors. At baseline visit, carotid atherosclerosis and ICAS were screened by color-coded duplex ultrasound, and moderate-severe stenosis was confirmed by magnetic resonance angiography. At baseline, 8.9% of subjects had asymptomatic ICAS, of whom 3.3% were moderate-severe. In the longitudinal phase, subjects were prospectively followed-up to assess the incidence of a combined primary endpoint of vascular events (stroke, acute coronary syndrome and/or vascular death). Results: After 7.17 years of follow-up, there were 51 incident cerebrovascular events (16 transient ischemic attacks, 27 ischemic, 8 hemorrhagic strokes), 63 incident coronary events and 23 vascular deaths. After multivariate Cox regression analyses adjusted by age, sex, vascular risk and presence of carotid plaques, ICAS was an independent predictor for overall vascular events (HR 1.83 [1.10–3.03], p  = 0.020), and moderate-severe intracranial stenosis was also an independent predictor for cerebrovascular events (HR 2.66 [1.02–6.94], p  = 0.046). Conclusions: Asymptomatic ICAS is independently associated with the incidence of future vascular events in our population. These findings might have implications for the development of primary prevention strategies.